Analysis of Natural and Induced Variation in Tomato Glandular Trichome Flavonoids Identifies a Gene Not Present in the Reference Genome . Issue 8 (15th August 2014) - Kim, Jeongwoon; Matsuba, Yuki; Ning, Jing; Schilmiller, Anthony L.; Hammar, Dagan; Jones, A. Daniel; Pichersky, Eran; Last, Robert L.
Abstract : Analysis of genomic resources, genetics, and biochemistry identified Sl-MOMT4 as a flavonol 3′ O- methyltransferase involved in the production of methylated flavonoids in glandular trichomes of the M82 cultivated tomato. This gene is missing in the tomato Heinz 1706 reference genome and represents an example of fast evolution of specialized metabolism genes among cultivated tomato varieties. Abstract: Flavonoids are ubiquitous plant aromatic specialized metabolites found in a variety of cell types and organs. Methylated flavonoids are detected in secreting glandular trichomes of various Solanum species, including the cultivated tomato ( Solanum lycopersicum ). Inspection of the sequenced S. lycopersicum Heinz 1706 reference genome revealed a close homolog of Solanum habrochaites MOMT1 3′/5′ myricetin O -methyltransferase gene, but this gene (Solyc06g083450) is missing the first exon, raising the question of whether cultivated tomato has a distinct 3′ or 3′/5′ O -methyltransferase. A combination of mining genome and cDNA sequences from wild tomato species and S. lycopersicum cultivar M82 led to the identification of Sl-MOMT4 as a 3′ O -methyltransferase. In parallel, three independent ethyl methanesulfonate mutants in the S. lycopersicum cultivar M82 background were identified as having reduced amounts of di- and trimethylated myricetins and increased monomethylated myricetin. Consistent with the hypothesis that Sl- MOMT4 is a 3′ O -methyltransferase gene, all three myricetin methylation defective mutants were found to have defects in MOMT4 sequence, transcript accumulation, or 3′- O -methyltransferase enzyme activity. Surprisingly, no MOMT4 sequence is found in the Heinz 1706 reference genome sequence, and this cultivar accumulates 3-methyl myricetin and is deficient in 3′-methyl myricetins, demonstrating variation in this gene among cultivated tomato varieties.